Janatha Aragalaya (the People’s Struggle) in Sri Lanka - A. R. M. Imtiyaz, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
On July 9, 2022, angry citizens, while protesting economic mismanagement, stormed the Sri Lanka’s President palace in Colombo. On July 13, President Gotabaya Rajapaksa escaped to the neighboring island nation of the Maldives and flew into Singapore from the Maldives on July 14 evening, after fleeing Sri Lanka amid a deepening crisis and widespread protests there. The primary objective of this paper is to provide some initial thoughts to the factors that led to the Aragalaya (struggle) and thus this article attempts to understand the major sources that gave birth to Janatha Aragalaya, commonly named by Sri Lankans as the GotaGoHome protest movement, significance of the movement and some suggestions to build democratic and peaceful Sri Lanka. The article first provides some primary information about the island’s demographics and socio-economic conditions. It then discusses the causes that gave birth to the protest movement. This section also attempts to provide some thoughts to understand why the state and its institutions such as security forces did not use violence against the movement. For the preparation of the article, the author conducted interviews with Sri Lankans who took part in the Aragalaya. Conversations were held in Tamil, Sinhala, and English speakers throughout the protests from April 12 to July 17 via WhatsApp and Facebook messengers.